Improving restoration heuristics to support anadromous fish passage - Sunny L. Jardine; Logan Blair; Catalina Burch; Andrew Cooke; Robert Fonner; Daniel S. Holland; J. Kahn; Connor Lewis-Smith; Luke W. Rogers; Mark D. Scheuerell; Braeden Van Deynze (PLoS ONE, 2026)
Investments in restoring river connectivity are growing worldwide to support freshwater biodiversity. Although optimization methods exist for selecting cost-effective restoration portfolios, decisions are often guided by simple heuristic rules. For example, managers may prioritize restoring barriers blocking the largest amounts of high-quality upstream habitat, ignoring the position of other barriers in the system. These heuristics often rely on proxies for watershed connectivity and habitat quality. Using anadromous fish passage restoration in western Washington, USA, as a case study, we show that redesigning these heuristics can yield substantial performance gains. Benchmarking common heuristics against optimization outcomes reveals that connectivity proxies based on total upstream habitat can achieve 93% of optimal gains when increasing habitat quantity is the sole objective, but adding widely used proxies for habitat quality (e.g., percent of upstream natural land cover) can cut performance nearly in half. These findings underscore the importance of designing heuristics that more directly target high-quality habitat gains to improve investment efficiency and help close the science–practice gap between optimization research and on-the-ground restoration decisions.